2022
DOI: 10.3390/antiox11020368
|View full text |Cite
|
Sign up to set email alerts
|

OxInflammation at High Altitudes: A Proof of Concept from the Himalayas

Abstract: High-altitude locations are fascinating for investigating biological and physiological responses in humans. In this work, we studied the high-altitude response in the plasma and urine of six healthy adult trekkers, who participated in a trek in Nepal that covered 300 km in 19 days along a route in the Kanchenjunga Mountain and up to a maximum altitude of 5140 m. Post-trek results showed an unbalance in redox status, with an upregulation of ROS (+19%), NOx (+28%), neopterin (+50%), and pro-inflammatory prostano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(75 reference statements)
0
7
1
Order By: Relevance
“…A growing body of evidence indicates that hypoxia decreases both the activity and effectiveness of the antioxidant system, as well as causing increased ROS production with a consequent increase in oxidative damage [ 3 ] to lipids [ 4 , 5 , 6 ], proteins and the DNA [ 5 , 7 ] of cellular compartments [ 8 , 9 , 10 ]. Most studies on the effects of hypoxia have been carried out at high altitude [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, under such conditions, several factors other than hypoxia could induce oxidative damage; UV radiation, intense physical activity and cold may in fact produce an imbalance between ROS generation and antioxidant protection [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that hypoxia decreases both the activity and effectiveness of the antioxidant system, as well as causing increased ROS production with a consequent increase in oxidative damage [ 3 ] to lipids [ 4 , 5 , 6 ], proteins and the DNA [ 5 , 7 ] of cellular compartments [ 8 , 9 , 10 ]. Most studies on the effects of hypoxia have been carried out at high altitude [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, under such conditions, several factors other than hypoxia could induce oxidative damage; UV radiation, intense physical activity and cold may in fact produce an imbalance between ROS generation and antioxidant protection [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding blood redox analyses, as reported, post-trek increases in ROS production rate, NOx, total Hcy, and GSH were detected; conversely, TAC and total Cys and CysGly decreased at Post [ 30 ]. The key result concerning the endocrine system was the impairment of the hypothalamic–hypophyseal axis.…”
Section: Resultsmentioning
confidence: 81%
“…Oxidative stress (OxS) is defined as the excessive production of ROS related to antioxidant defence and can be triggered by endogenous and exogenous factors, among which are expeditions to high altitudes. In fact, exposure to high altitude has been associated with an increase in ROS and related oxidative damage [ 10 , 11 , 30 , 32 ] induced by environmental factors such as hypoxia, cold, UV ray, exposure, and/or physical exercise (daily frequency, low-middle intensity, high volume) [ 30 ]. Moreover, Agarwal et al reported that several extrinsic or environmental factors, such as ionising radiations, alcohol, obesity, deficiencies in antioxidants, varicocele, bacterial/viral infections, toxins, and chemotherapy can induce testicular ROS, causing abnormal spermatogenesis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under hypobaric hypoxic conditions, the crosstalk between oxidative stress and inflammation is important. Studies have demonstrated positive feedback between oxidative stress and inflammation, which recently has been coined “oxinflammation” [ 36 , 37 ]. Therefore, based on the mentioned evidence, there is an important role of inflammation under hypoxic conditions that could affect different tissues and organs, including the lung ( Figure 1 ), which will be discussed below.…”
Section: Hypoxia and Inflammationmentioning
confidence: 99%